2001
DOI: 10.1021/jo0011179
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Configuration, Predominant Conformations, and Vibrational Circular Dichroism Spectra of Enantiomers of n-Butyl tert-Butyl Sulfoxide

Abstract: Alkylation of the alpha-carbanion of (R)-(-)-tert-butyl methyl sulfoxide (4) with n-propyl bromide afforded (+)-n-butyl tert-butyl sulfoxide (1) to which the absolute configuration (R) was ascribed. This assignment was confirmed by X-ray analysis of the complex 6 obtained from the enantiomerically pure sulfoxide (-)-1 and mercury chloride. Vibrational absorption and circular dichroism spectra of (+)-1 were measured in CDCl3 solution in the 2000-900 cm(-1) region and compared with the ab initio predictions of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…VCD studies of other chiral sulfoxides are currently in progress. [37,38] Experimental Section Synthesis Racemic tert-butyl methyl sulfoxide [(AE)-1] was prepared according to the literature procedure. [39] The dextro-and levorotatory enantiomers of tertbutyl methyl sulfoxide (1) were prepared using the diastereomeric sulfinates derived from (À) diacetone glucose (DAG).…”
Section: Resultsmentioning
confidence: 99%
“…VCD studies of other chiral sulfoxides are currently in progress. [37,38] Experimental Section Synthesis Racemic tert-butyl methyl sulfoxide [(AE)-1] was prepared according to the literature procedure. [39] The dextro-and levorotatory enantiomers of tertbutyl methyl sulfoxide (1) were prepared using the diastereomeric sulfinates derived from (À) diacetone glucose (DAG).…”
Section: Resultsmentioning
confidence: 99%
“…57 Polavarapu et al 58 at Vanderbilt University have investigated several volatile anesthetics, including 1,2,2,2-tetrafluoroethyl methyl ether, enflurane, 59 and a degradation product of sevoflurane (1,1,1,3,3-pentafluoro-2-(fluoromethoxy)-3-methoxypropane). 60 Conformations of (R)-( -)-2-butanol, 61 (S)-( -)-3-butyn-2-ol, 62 (+)-epichlorohy-drin, 63 (2R,3R)-( -)-2,3-butanediol 64 were elucidated with VCD and the configurations and conformations of a series of phenyl oxides and sulfoxides have also been reported, including tert-butylphenylphosphine oxides, 65 n-butyl-tertbutyl sulfoxide, 66 (+)-2,5-dimethylthiolane and (+)-2,5-dimethylsulfolane, 67 tert-butylphenylphosphinothioic acid, 68 tert-butyl-1-(2-methylnaphthyl)phosphine oxide, 69 and (S)-(+)-3-(2-methylbutyl)thiophene, (+)-3,4-di[(S)-2-methylbutyl)]thiophene, and polymers. 70 These studies surveyed 6-31G*, 6-31+G, 6-311G(2d,2p), 6-3111G(2d,2p) and 6-331G(3df,3dp) basis sets for these molecules.…”
Section: Recent Applications Of Stereochemical Determinationmentioning
confidence: 99%
“…For this purpose, we have developed a conformational code for the exhaustive analysis of conformers of all kinds of molecules. 10 At the time that we started our VCD conformational studies, Polavarapu and coworkers reported density functional theory (DFT) calculations of VCD for various flexible compounds such as (1)-enflurane, 13 (2)tert-butylphenylphosphine oxide, 14 (2)-2-butanol, 15 (1)-nbutyl tert-butyl sulfoxide, 16 (1)-2,5-dimethylthiolane, 17 (2)-2,3-butanediol, 18 tert-butylphenylphosphinothioic acid, 19 3-(2-methylbutyl)thiophene, 20 1,1,1,3,3-pentafluoro-2-(fluoromethoxy)-3-methoxypropane, 21 bromochlorofluoromethane, 22 tert-butyl-1-(2-methylnaphthyl)phosphine oxide, 23 and (1)-1-bromo-2-methylbutane. 24 As a result, we decided to carry out VCD theoretical calculations for additional large chiral compounds such as (1)-2-hexanol, (1)-2-heptanol, (1)-2-octanol, (1)-2-nonanol, and (1)-2decanol.…”
Section: Introductionmentioning
confidence: 99%